المنهجية الأصولية عند الإمام أبي الحسن الأشعري: عرض وتحليل Al-Imam Abu al-Hasan al-Asha'ris Approach in Usul al-Fiqh: An Analytical Survey - إمام (Mohamed Kamal Imam), محمد كمال (At-Tajdid - Intellectual Refereed Journal, 2010)
مستخلص البحث إن المنهجية الفكرية التي أرسى قواعدها أبو الحسن الأشعري (المتوفى سنة 324 للهجرة) والتي تطورت على أساسها المدرسة الأشعرية في علم الكلام ودرس مسائل العقيدة وعرضها قد كان أثر كبير وامتدادت كثيرة في مجالات أخرى كثيرة من مجالات الفكر الإسلامي، وخاصة علم أصول الفقه. وإذا كان تراث الأشعري وآراءه في مسائل جليل الكلام ودقيقه قد جرت دراستها في سياقات مختلفة، إلا أن ما يتعلق بالفقه وأوصوله (أو علم الفروع) لم يلق القدر نفسه من عناية الباحثين. وسعيًا للإسهام في سد ولو جزء سيسير من هذا النقص، يحاول الباحث أن يقدم عرضًا وتحليلاً أوليًّا لآراء الأشعري في بعض أمهات المسائل لعلم أصول الفقه علها تكون حافزًا لبحوث أكثر استقصاءً وأبعد غورا. الكلمات الأساسية: الأشعري، علم الكلام، الفقه، الاجتهاد، أصول الفقه، الأشاعرة، المعتزلة. السودان Abstract The intellectual approach whose foundations had been laid down by AbË Al-×asan al-Ash‛arī (d. 324H) and according to which the Ash‛arite school was shaped with regard to theology and the study and exposition of the matters of belief has had a great impact and many ramifications in many other fields of Islamic thought, especially Islamic jurisprudence and legal theory. Although al-Ash‛arī’s legacy and views pertaining to divine (jalīl) and natural (daqīq) issues in theology have been the subject of several studies, his views concerning issues of jurisprudence and legal theory have received less scholarly attention. Therefore, the present author attempts to provide an elementary analytical exposition of al-Ash‛arī’s thoughts on some major issues of Islamic legal theory (uÎËl al-fiqh) with the hope that it could motivate more comprehensive and profound research in this regard. Key terms: al-Ash‛arī, Islamic theology, Islamic jurisprudence, ijtihād, Islamic legal theory, the Ash‛arites, the Mu‛tazilites. Abstrak Landasan pemikiran yang diletakkan oleh Abu al-Hasan al-Asy'ari (wafat 324 Hijrah), adalah merupakan dasar untuk perkembangan sekolah pemikiran teologi Mazhab al-Asy'ari. Ia mempunyai pengaruh yang besar dalam hal yang berkaitan dengan asas-asas iman namun ia juga telah mempengaruhi beberapa aspek pemikiran Islam yang lain khususnya ilmu Fiqh. Walaupun warisan ilmu al-Asy’ari dan pandangannya tentang masalah teologi telah diteliti dalam konteks yang berbeza, malangnya pandangannya tentang Fiqh dan cabangnya yang lain masih tidak mendapat perhatian yang menyeluruh daripada golongan pengkaji. Untuk menutup jurang perbezaan ini, kajian ini akan cuba untuk mengatasi kekurangan ini melalui satu pembentangan dan analisis awal terhadap pandangan al-Asy'ari dalam beberapa isu utama di dalam bidang Fiqh yang mungkin dapat menjadi pemangkin kepada kajian-kajian yang lebih lanjut berkenaan degannya pada masa hadapan. Kata kunci: Ilmu Kalam al-Asy'ari, Doktrin, Fiqh, ijtihad, Usul-Fiqih, Mu'tazilah, Sudan, tasawuf.